Urban water reuse handbook - Eslamian, Saeid (CRC Press, Taylor & Francis Group, 2016)
"Examining the current literature, research, and relevant case studies, presented by a team of international experts, the Urban Water Reuse Handbook discusses the pros and cons of water reuse and explores new and alternative methods for obtaining a sustainable water supply. The book defines water reuse guidelines, describes the historical and current development of water reuse, and includes previously implemented methodologies and practices relevant to urban wastewater treatment. It considers the sustainability of water resources and supply systems in both urban and rural areas. The book discusses the advantages of water reuse (reduced water consumption, cost-savings, a secure groundwater replenishment source, and a long-term water supply) and outlines the disadvantages (a build-up of chemical pollutants in the soil, the probable contamination of groundwater attributed to reclaimed water, and possible human health risks related to the presence of viruses and bacteria). It also proposes ethical and cultural considerations, discusses the economic and environmental performance of water systems relevant to water reuse, and outlines associated methods and strategies that can address problems of water scarcity. In addition, this handbook addresses: Constructed wetlands in surrounding urban areasWater reuse in specific regions, coastal areas, cold regions, arid zonesApplication of wastewater for hydroelectric power generationTraditional systems of water reuseCombining harvesting systems and water reuse structuresWarning systems for wastewater access controlPublic participation and implementation issuesGroundwater recharge by unconventional waterUrban water reuse policyA resourceful guide dedicated to the reuse of urban wastewater, the Urban Water Reuse Handbook focuses on wastewater treatment, recycling, and reuse for the conservation of water resources. This book serves as a reference for water resource engineers, urban hydrologists, and planning professionals; for water/wastewater engineers, students, policy makers, and researchers."--Provided by publisher
Keywords: Water reuse -- Handbooks, manuals, etc.; Municipal water supply -- Handbooks, manuals, etc.; elektronické knihy; electronic books